Respostas de clones de batata ao armazenamento em baixas temperaturas e ao recondicionamento - Cavallin, Isabella Cristina (2016)
The consumption processed potato (Solanum tuberosum L.) is constantly on rise in Brazil. However, the producers of processing industry of potato have found difficulties to the supply of high quality raw material during the whole year, especially when the averages temperatures are higher, causing a reduction in productivity of dry matter. Thus, an alternative to ensure the quality of the potato for the processing would be to storage at cold the tubers produced in the most favorable seasons (winter season). Nevertheless, the storage at low temperatures causes changes in the quality of raw materials, particularly the accumulation of reducing sugars (glucose and fructose), called as cold-induced sweetening (CIS). To reverse this reaction of sweetening caused in the tubers, the industry uses a procedure called the reconditioning. Potato clones from the breeding program of Universidade Federal de Lavras (UFLA) were assessed for their agronomic performance and their behavior when stored at low temperatures and reconditioned. Reducing sugars, starch content, specific gravity, and color of pulp and fried sticks were quantified in the laboratory, while the agronomic characteristics such as productivity of large tubers, dry matter yield, specific gravity, color of pulp and fried sticks were evaluated in the field trials. It was possible to select clones with the ability to recondition after submitted to low temperatures, besides having good agronomic characteristics. Clones with the capacity for the processing for chips industry are IND 04-22, IND 07-59, and IND 01 -83 and the GMR 18-20, GMR 24-09, IRF 03-45 and IRF 13-02 have the ability for the frozen frying industry.